OLEXANDER DOVZHENKO – EXTRAORDINARY NOBLE AND TRAGIC FIGURE - Геник, C. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Literature’s review of life and work of Olexander Dovzhenko, his triumph, cascade of tragedies and crossroad are presented. Partial analysis of special service’s declassified documents and his diaries is given. It is emphasised that in his work Olexander Dovzhenko outlined the power of national idea, it’s history and unifying tendency, that inspired us and give us power to struggle and create future.